1999
DOI: 10.1183/09031936.99.13108399
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in school-aged asthmatic children with inhaled cromoglycate, nedocromil and corticosteroid therapy

Abstract: Two-thirds of the children with asthma in our area use cromones and only one-third steroids as the maintenance therapy. This study aimed to evaluate our treatment policy based on the international consensus. Peak expiratory flow (PEF), dynamic spirometry and bronchodilation test results were therefore collected in 195 school-aged patients who visited our outpatient clinic in 1995. Sixty-four children (33%) used cromoglycate, 86 (44%) nedocromil and 45 (23%) inhaled steroids. Twenty-five (12%) needed combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…Our results suggest that the difference in the numbers of readmissions was attributable to good symptom control of asthma by the inhaled steroids. The result is at odds with our earlier observations, which indicated that good symptom control, evaluated objectively by lung function measurements, could also be achieved by cromones in as many as 50 to 70% of children suffering from asthma (27). However, on closer examination, these results are not necessarily contradictory and, in fact, are in agreement with a study from Belgium (28).…”
Section: Discussioncontrasting
confidence: 71%
“…Our results suggest that the difference in the numbers of readmissions was attributable to good symptom control of asthma by the inhaled steroids. The result is at odds with our earlier observations, which indicated that good symptom control, evaluated objectively by lung function measurements, could also be achieved by cromones in as many as 50 to 70% of children suffering from asthma (27). However, on closer examination, these results are not necessarily contradictory and, in fact, are in agreement with a study from Belgium (28).…”
Section: Discussioncontrasting
confidence: 71%
“…19 First, the children were carefully instructed on how to perform the test. The result of at least 75% of that of predicted was regarded as a normal.…”
Section: Pulmonary Function Testingmentioning
confidence: 99%
“…According to our guidelines, children with mild-to-moderate asthma are treated with cromones and those with severe symptoms or those not responding to cromone therapy are treated with inhaled steroids. 19…”
Section: Definition Of Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…One study has followed children on both cromolyn sodium and on inhaled corticosteroids for prolonged periods (up to 16.8 years) and found no evidence of irreversible airway changes in either group [ 42]. Korhonen and colleagues report a study in 195 children in which treatment with cromolyn sodium or nedocromil resulted in pulmonary function tests no different from those treated with inhaled corticosteroids [ 43].…”
Section: Clinical Comparisonsmentioning
confidence: 99%